Rancang Bangun Aplikasi Pembuatan Laporan Laba Rugi Pada ASTRANS Logistics - Kurniawan, Rizky; Jusak, Jusak; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Abstract:ASTRANS logistics is a service company in logistic transport based in Jl. Perum Gading Fajar II Blok D2 No.10 Sidoarjo which is doing shipment in Java, Bali and West Nusa Tenggara. ASTRANS Logistics hasn’t done good financial accounting standard yet. All income, outcome and loan recorded manually by ASTRANS Logistics using Microsoft Excel as a tool to calculate. All payment done made by the shipper or the recipient are not optimal. So, small cash balance difference and company cash in a bank is often occurred.As a solution for this problem, in this work, we develop or statement web-based that will assist the company in producing accurate financial statement.It is shown that the new application has the capability in determining customer payment, accounts receivable maturity date, income statement and performing daily closing, and test Alfa for 42 function and then get validation 100% comfortable with Software Requirement Specification (SRS).